Petromyopia: Oil and the Energy Humanities - Christopher F. Jones (Humanities, 2016)
Oil is currently over-represented in the energy humanities, a state of affairs I describe as petromyopia. While oil constitutes a vital source of energy in the modern world, focusing too heavily on petroleum can distract scholars from giving proper attention to other aspects of the social and cultural dimensions of energy. The goal of this article is to encourage those in the energy humanities to cast a broader net in their analyses and recognize the full diversity of energy systems in their scholarship.